Influence of cochlear implantation on vestibular function. (2nd July 2016) - Chen, Xiulan; Chen, Xiaohua; Zhang, Fan; Qin, Zhaobing
Abstract: Conclusion Vestibular function in patients can be damaged following cochlear implantation. Therefore, assessing the pre-operative vestibular status, carefully choosing the side of implantation, and preserving function by using minimally invasive surgical techniques are important.Objectives The aim of this study was to assess the influence of cochlear implantation on vestibular function in patients with severe and profound sensorineural hearing loss, and to analyze a possible correlation between the changes in vestibular testing and post-operative vestibular symptoms.Methods Thirty-four patients were evaluated for vestibular function using the cervical and ocular vestibular-evoked myogenic potentials (cVEMP and oVEMP, respectively), and 29 patients underwent caloric tests pre-operatively and 4 weeks post-operatively.Results Before surgery, the cVEMPs were recorded bilaterally in 22 patients, unilaterally in eight patients, and absent bilaterally in four patients. The oVEMPs were recorded bilaterally in 19 patients, unilaterally in six patients, and absent bilaterally in nine patients. After implantation, the cVEMPs were absent in 10 patients and the oVEMPs were absent in seven patients on the implanted side. Caloric tests demonstrated canal paresis in 17 patients, and normal responses were recorded in 12 of the 29 patients pre-operatively. There was a significant decrease post-implantation in the ear implanted, with the exception of two patients. Two patients presented with vertigo and another two patients reported slight unsteadiness post-operatively, but all symptoms resolved within 7 days. The impaired vestibular function did not correlate with vestibular symptoms, age, or gender. Function on the contralateral side remained unaffected.